PEMBUATAN OTAK – OTAK BANDENG DI DESA LOMULI KABUPATEN POHUWATO : PEMBUATAN OTAK – OTAK BANDENG DI DESA LOMULI KABUPATEN POHUWATO - Ria Megasari (Program Vokasi Universitas Negeri Gorontalo, 2022)
Milkfish is a herbivore fish, cultivated and often traded in the community. For some people, there are people who don't like milkfish because it has too many spines, even though the nutritional value of milkfish is higher than chicken. To overcome this problem, the development of processing milkfish into milkfish brains was carried out. The people of Pohuwato, especially the Sinar Lomuli IKM group in Lomuli Village, consume milkfish only as a side dish to accompany rice, usually cooked or grilled. The purpose of this activity is to improve HR skills and competencies, wider marketing and longer shelf life and better management. Based on observations and interviews conducted by the PKM Team with partners, there are several problems faced by Partners, namely: 1) No have the skills to process milkfish into processed products 2) Products do not yet have a market. The solutions offered by the PKM Team to the Partners are as follows: 1) The IKM groups who participated in the training gained new skills in processing milkfish. 2) Sinar Lomuli IKM can promote and sell their products offline and online.